THREE TABLES FOR BOB. (28th September 2016) - Sabat, Marc
Abstract : To distinguish differences of harmony, to compose music so that players and listeners may sense these variations naturally, in real time, the representation of harmonic space in musical notation must be precise yet simple to read. Shadings of intonation are most clearly conceived in relation to consonant, untempered intervals. Intervals derived from a common frame of reference may be represented by microtonal signs, which suggest potentially tuneable intervallic relationships.